Physical Anthropology - Philip L. Stein; Bruce M. Rowe; Brian Pierson (New York : New York McGraw-Hill Education, 2020)
"What is new in the twelfth edition? Physical anthropology is a dynamic field. We have updated the entire book on the basis of new information. This is seen most clearly in the chapters on human genetics (Chapters 2 and 3). In the last several years, our knowledge of human genetics has increased enormously. We reorganized, rewrote, and streamlined Chapters 2 and 3 to reflect the new information in genetics that was relevant to physical anthropology. Other areas of significant revision were the chapters on the fossil record of human evolution (Chapters 12 to 15). Again, we included new information that has been published in recent years, but not all of that information. The fact that new information and ideas are published does not necessarily mean that the significants of those finding and concepts are immediately known. So, we did not include every new finding and idea in this edition. An example of why we choose not to include everything might be made clear with something that happened just as the 10th edition of this book was being prepared, a 47-million-year-old fossil, Darwinius massillae, which was nicknamed 'Ida,' was touted as 'the missing link' in human evolution. The Internet and print media were full of claims and speculation, much of which either was not true or played on the public's misunderstanding of evolution, especially the misconception of a 'missing link.' Ida has little significance to the understanding of human evolution. We hope that after students complete a course in Physical Anthropology, they will recognize illogical or factually incorrect statements made in the name of evolutionary theory in the popular media"-- Provided by publisher
Keywords: Anthropologie physique; physical anthropology